Management and Minimisation of Uncertainties and Errors in Numerical Aerodynamics Results of the German collaborative project MUNA - Eisfeld, Bernhard; Barnewitz, Holger; Fritz, Willy; Thiele, Frank; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This volume reports results from the German research initiative MUNA (Management and Minimization of Errors and Uncertainties in Numerical Aerodynamics), which combined development activities of the German Aerospace Center (DLR), German universities and German aircraft industry. The main objective of this five year project was the development of methods and procedures aiming at reducing various types of uncertainties that are typical of numerical flow simulations. The activities were focused on methods for grid manipulation, techniques for increasing the simulation accuracy, sensors for turbulence modelling, methods for handling uncertainties of the geometry and grid deformation as well as stochastic methods for quantifying aleatoric uncertainties.
Part I Mesh Generation and Manipulation -- Part II Turbulence Modeling -- Part III Numerical Methods -- Part IV Geometry and Deformation -- Part V Stochastic Uncertainties.
Keywords: Engineering; Materials; Engineering; Continuum Mechanics and Mechanics of Materials; Numerical and Computational Physics; Fluid- and Aerodynamics